Hungarian Monitoring, 26 February 1990 . [Magyar rádiófigyelő], 1990. február 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Sajudis victory in Lithuanian elections - Nicaragua: secret negotiations with the US, elections - Fascists also make their appearance in Poland; visit of the Israeli foreign minister - Soviet troop withdrawals from Czechoslovakia start today; Havel in Moscow - Bush and Kohl favor Germany's membership of NATO - Vienna disarmament talks Domestic Affairs: - Government in session: Party property, Soviet troop withdrawals, Kossuth and Széchenyi prizes, taxing interest - Mátyás Szűrös negotiates more national summit meetings with the leaders of four parties - Military supreme prosecutor completes investigation against colleagues in internal security service - Elections: Medián's opinion poll, Spanish election experts, National Election Committee - Many parties protest against TV broadcast of Miklós Németh's March 15 speech - Break-in at Budapest HQ of Independent Smallholders', Agrarian Workers and Civic Party (FKGP) Economy: - Protest by Ikarusz employees - Familiar faces fill joint company managing directors' posts Külpolitika: - Litvániában győzött a Szajudisz - Nicaragua: titkos tárgyalások az USA-val, választások - Lengyelországban is megjelentek a fasiszták; az izraeli külügyminiszter látogatása - Ma megkezdődtek a szovjet csapatkivonások Csehszlovákiából; Havel Moszkvában - Bush és Kohl az egyesített Németország NATO tagsága mellett - Bécsi leszerelési tárgyalások Belpolitika: - Kormányülés: pártvagyon, szovjet csapatkivonás, Kossuth és Széchenyi díjak, kamatadó - Szűrös Mátyás négy párt vezetőjével az újabb nemzeti csúcstalálkozóról tárgyalt - A katonai főügyészség befejezte a nyomozást a belső biztonsági szolgálat munkatársai ellen - Választások: a Medián közvélemény kutatása, spanyol választási szakemberek, OVB - Több párt tiltakozik az ellen, hogy a TV közvetítse Németh Miklós márc. 15-i beszédét - Betörtek a Független Kisgazda Párt budapesti székházába Gazdaság: - IKARUSZ dolgozók demonstrációja - Ismerős arcok a vegyesvállalatok vezérigazgatói székében